Misogynistic Values in Indonesian Horror Films (Critical Discourse Analysis of Sarah Mills on the Film Rumah Dara) - Rana Akbar Fitriawan; Haris Annisari Indah NR; Wa Ode Suci Rahmayani (Eduvest - Journal of Universal Studies, 2025)
This study aims to analyze the representation of women in the Indonesian horror film "Rumah Dara" and deconstruct the discourse contributing to the formation of misogynistic values. The background issue is gender relations marked by inequality and injustice in patriarchal societies, where women are often subordinated. Misogyny, manifesting in various forms of discrimination and violence, frequently appears in social and cultural contexts that position women lower than men. The method used in this study is Sarah Mills' Critical Discourse Analysis, which examines the interaction of language, power, and ideology in shaping social practices and the structure of female character representation. The findings reveal that characters in this film not only play narrative roles but are also influenced by the subject's perspective. This is evident in various scenes depicting the objectification and violence against women, reflecting patterns of gender domination and oppression. The implications of this research highlight the significant role of film media in shaping and reinforcing anti-women attitudes in society and the importance of critical analysis in examining gender representation in media.